The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18535/ijsrm/v5i9.20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Relaxation Handheld Fingertechnique and Benson Relaxation to the Changes Level of Post Operative Pain Sectio Caesarea in Rsi Sakinah Mojokerto

Abstract: Pain after major or minor surgery will impact the anatomical and physiological changes in patients. Givinganesthetic is not always sufficient to eliminate the sensation of pain because the pain response of eachpatient is different. Postoperative pain caesarea section must be solved with non-pharmacological methodsof handheld eg relaxation techniques and relaxation benson finger. The purpose of this research was toprove efektikitas between both these relaxation techniques to changes in the level of postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
1
Order By: Relevance
“…5,13,31,32 However, few studies have compared the two groups used in the current research. In two studies comparing foot reflexology and hand reflexology with Benson relaxation, reflexology had a higher impact on pain reduction, 23,25 which is not consistent with our findings. This discrepancy might be due to the process of Benson relaxation, which is controlled by the participants.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…5,13,31,32 However, few studies have compared the two groups used in the current research. In two studies comparing foot reflexology and hand reflexology with Benson relaxation, reflexology had a higher impact on pain reduction, 23,25 which is not consistent with our findings. This discrepancy might be due to the process of Benson relaxation, which is controlled by the participants.…”
Section: Discussioncontrasting
confidence: 96%
“…20,21 Studies have demonstrated the effect of this method on different pains. 5,[22][23][24] A few studies have compared the effect of the relaxation method with reflexology. In a study by Mokhtari Noori et al, foot reflexology and relaxation effectively reduced pain in patients following a C/S; and reflexology had a higher impact on pain alleviation.…”
Section: Introductionmentioning
confidence: 99%